MAKNA GERAKAN SOSIAL MEME â€œJOKOWI: THE KING OF LIP SERVICEâ€ PADA AKUN INSTAGRAM BEM UI - Sibaweh, Nurdin; Cangara, Hafied (Laboratorium Ilmu Komunikasi, Fakultas Ilmu Sosial dan Ilmu Politik (FISIP) Universitas Ha, 2021)
Along with the development of technology and the emergence of new media, the form of social movement has also developed into not only physical action and mass movements on the street, but it has turned into new kind of actions with more varied forms of movement.Â such as movement through social media and memes on Instagram. On June 26, 2021, BEM UI through @bemui_official instagram account, had brought up the meme